The Importance of Local Communities in Addressing the Healthcare Human Resources Crisis in Remote Areas - Rahmadhani, Alda Adiestya; Hasanbasri, Mubasysyir (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to address the crisis of healthcare human resources in remote areas of Indonesia by exploring the potential of utilizing local communities to mitigate these challenges. The primary objective is to propose strategic measures to enhance the distribution and sustainability of healthcare professionals in these underserved regions. Method: The research reviewing existing policies, healthcare workforce distribution data, and the organizational structure of primary healthcare centers (Puskesmas) in remote areas. The analysis focuses on the integration of Mintzberg's organizational theory, emphasizing the importance of the Operating Core, which comprises healthcare providers directly involved in patient care. Data were collected through literature reviews and policy analysis. Results: The findings reveal significant disparities in the distribution of healthcare workers between urban and remote areas. Factors contributing to this imbalance include a lack of interest in working in remote locations, insufficient continuous professional development, and inadequate welfare support for healthcare workers in these regions. The study identifies the necessity of updating local government policies, specifically the remote area service decrees (SK Keterpencilan), to better reflect the current needs and conditions. Moreover, integrating local community members into the healthcare workforce is suggested as a sustainable solution. This includes recruiting local individuals through existing government programs like Nusantara Sehat, providing tailored educational programs, and enhancing supportive facilities and incentives for healthcare workers. Conclusion: To address the healthcare HR crisis in remote areas, it is crucial to revise existing policies, promote the involvement of local communities, and ensure adequate support and training for healthcare professionals. Implementing these strategies can improve the sustainability and efficiency of healthcare services in remote areas, ultimately enhancing health outcomes for these underserved populations.